Effectiveness Of The Sets Learning Model On Elementary School Students Concept Application Abilities - Belvana, Salvia; Sutisnawati, Astri; Lyesmaya, Dyah; Uswatun, Din Azwar (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
The problem that occurs is that the learning process still uses conventional learning models which are monotonous, only listening, seeing, taking notes, and not always using practice so that it does not provide a strong understanding and is not impressive. Most students are less sensitive to the conditions that occur in their environment, which makes it difficult for students to feel the ability to apply concepts. This research aims to determine the effectiveness of the Science Environment Technology and Society (SETS) learning model on Elementary School Students' Concept Application Ability. Using quantitative methods, Quasi Experimental research type. The population is class IV students at SDN Kadudampit. The sampling technique uses Stratified Random Sampling, namely class IV samples have two class groups, namely class A as the experimental class and class B as the control class. Data collection uses a 10-question multiple choice test. Data analysis using the two independent sample t test obtained a sig value. 0.023 0.05 then Ha in this study is accepted, namely that there is a significant difference between the experimental class and the control class. And testing effectiveness using the N-gain Score test produced an average score for the experimental class of 67.41% in the "Quite Effective" category, while the control class average was 50.2% in the "Less Effective" category. So it can be concluded that there is effectiveness of the Science Environment Technology and Society (SETS) learning model on Elementary School Students' Concept Application Ability.